David Foster Wallace's balancing books : fictions of value - Severs, Jeffrey, 1974- (Columbia scholarship online., 2017)
"Jeffrey Severs offers one of the first critical works that examines the entirety of David Foster Wallace's fiction rather than individual novels. Severs focuses his interpretation of Wallace's work on the author's interest in "value" understood in terms of the incalculable (morality) and the calculable (economics). This approach, Severs argues, allows a reading of Wallace that illuminates both the philosophical and moral ambition of his work but also positions him as a writer very much engaged in the political and economic issues of the late twentieth century. Severs reads Wallace as depicting characters struggling to determine the moral authority amid our chaotic culture. In considering the full scope of Wallace's career, Severs details his works' quest for balance in a world of excess and entropy. He adds to the critical portrayal of him as the philosopher-novelist by reading him as not only satirizing the deforming effects of money but examining the machinations of late-capitalism. Fusing readings of metaphysical, existential, and moral themes within the historical context of the last twentieth century, Severs provides new perspectives on Wallace's work and demonstrates the relevance of his fiction to contemporary political, economic, moral, and ethical problems."--